Etude De L’Activité Antioxydante Des Huiles Essentielles De Plantes Aromatiques Et Médicinales Marocaines - Ismaili, Rachid; Houbairi, Sara; Sanâa, Lanouari; Khadija, Moustaid; Abdeslam, Lamiri (European Scientific Journal, ESJ, 2017)
Morocco is a traditional supplier of medicinal and aromatic plants to the world. This activity has resulted to the exploitation of wild plants than dried plants for herbal needs and food flavors. Many species are used for the production of plant extracts and other aromatic essences mainly for the pharmaceutical and cosmetics industry. Among these metabolites, there are essential oils that are mixtures of aromatic substances present in the form of tiny droplets in the leaves, fruit peel, resin, branches, and wood. These oils, however, is endowed with antioxidant properties. This study aims to evaluate the antioxidant activity of essential oils of three moroccan aromatic and medicinal plants: Thymus vulgaris, Mentha spicata, and Citrus limonum. The oil extraction was performed by steam distillation in a Clevenger type apparatus. Also, the antioxidant activity of these oils was evaluated by the method of DPPH (2,2-diphenyl-1-picrylhydrazyl), in comparison with the antioxidant synthetic, ascorbic acid. In the present work, the results showed that the antioxidant activity of three essential oils studied by the trapping method of free radical is moderate. Also, the oil of Thymus vulgaris has a strong activity which exceeds that of ascorbic acid. This was followed by the oil of Mentha spicata, while the lowest activity was observed in Citrus limonum.